Principles of exposure measurement in epidemiology collecting, evaluating, and improving measures of disease risk factors - White, Emily, 1946-; Armstrong, B. K.; Saracci, Rodolfo, 1936-; Armstrong, B. K. (Oxford : Oxford University Press, 2008)
Accurate measurement of exposure to putative causes of disease is essential to the validity of epidemiologic research. This is a new edition of a unique book outlining the principles and techniques of exposure measurement.
Previous ed.: published as by Bruce Armstrong, Emily White, Rodolfo Saracci. 1992.
Description based on print version record.
Includes index.
Keywords: Epidemiology -- Methodology